Dynamic behaviour of long span cantilever steel-concrete composite floor - Amisah Ahwang, author; Norhaya Ahmad; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Kejuruteraan (Struktur) - Universiti Teknologi Malaysia, 2017